Counter charge cluster formation in molecular doping of molybdenum disulfide - Lee, Jonghoon; Kedziora, Gary; Glavin, Nicholas; Roy, Ajit K. (Frontiers in Carbon, 2023)
Studies of molybdenum disulfide (MoS2) gas sensor prototypes report orders of magnitude higher sensitivity toward nitrogen dioxide (NO2) over ammonia (NH3). Based on the cluster formation model and density functional theory calculations of charge transfer, NO2 was found to form a tightly bound cluster of counter charges upon carrier donation. In contrast, NH3 forms only a semi-localized cluster of counter charges over a wide area of MoS2, creating a larger collision cross section of coulomb interaction between the charge carrier and the counter charges. We discuss the potential effect of counter charge cluster localization on the efficiency of molecular doping.